Contamination of Bacillus cereus in Foods Sold at Ramadan Bazaar in Kuching, Sarawak: Bacillus cereus in foods at Ramadan bazaar - NURUL AZYLA AZMI; SHARIFAH AMINAH SYED MOHAMAD; ABU MUSLIM AHMAD; NAJIHAH MOHD SANI; SITI ROHA AB MUTALIB; FAZDLINA SAPEE (Borneo Journal of Resource Science and Technology, 2023)
Every year there are reports of food poisoning involving food sold at the Ramadan bazaar and one of the causes of food poisoning is Bacillus cereus. This study aimed to determine the contamination level of B. cereus and the antimicrobial susceptibility profile of the isolates in food sold at Ramadan bazaar in Kuching, Sarawak. A total of 155 samples from five food categories were collected from six Ramadan bazaars in three locations around Kuching. Overall, 32 (21%) food samples were found positive for B. cereus. Cooked rice showed the least satisfactory levels of B. cereus among the food categories and nasi lemak was the type of food that highly contaminated with B. cereus. Antibiotic susceptibility assessment showed that B. cereus isolates were highly resistant to ampicillin, amoxicillin/clavulanic, penicillin and cefotaxime in this study. The findings of this study showed that B. cereus has the potential to cause food poisoning to Ramadan bazaar consumers due to the high mean count in some types of food. Therefore, this study can be used as basic data for B. cereus control measures in food sold at the Ramadan bazaar.